Shear behaviour of cold-formed stainless-steel beams with web openings: Numerical studies. (June 2021) - Ishqy, Muhammadh Fareedh Muhammadh; Wanniarachchi, Somadasa; Poologanathan, Keerthan; Gunalan, Shanmuganathan; Gatheeshgar, Perampalam; Suntharalingam, Thadshajini; Navaratnam, Satheeskumar
Abstract: Cold-formed stainless-steel (CFSS) sections are increasingly popular for architectural and structural applications, especially in the corrosive environment due to its resistance to corrosion and other various benefits. The combination of stainless-steel material properties and the lightweight section properties makes the CFSS section the right choice for offshore steel structures. The demand for the stainless-steel sections in the construction industry is limited to a certain extent due to the higher cost; thus, the optimal use of stainless steel is vital. Openings to the web of CFSS Lipped Channel Beams (LCB) are introduced to facilitate the building services to reduce the floor height. Subsequently, the shear capacity is reduced due to the reduction of the web area. However, only very limited researches have been conducted so far to predict the reduced shear capacity of CFSS LCBs with circular web opening. Hence, this paper addresses a numerical study to investigate the shear behaviour and strength of cold-formed austenitic grade 1.4301 and duplex grade 1.4462 stainless steel LCB sections with unreinforced circular web openings. A detailed parametric study was carried out by developing 180 Finite Element Analyses (FEA) models to establish a wide-ranging shear strength database following the validation process with available shear test results. The analysis of the numerical results showed that the currently available reduction factor equations are either conservative or unsafe to use for the CFSS LCBs with circular openings. Hence, three sets of equations with different approaches to predict the shear capacity of CFSS LCBs with circular web opening are developed and presented in this paper.